Direct Lateral Lumbar Interbody Fusion: Clinical and Radiological Outcomes - Lee, Young Seok (The Korean Neurosurgical Society, 2014)
OBJECTIVE: According to the recent development of minimally invasive spinal surgery, direct lumbar interbody fusion (DLIF) was introduced as an effective option to treat lumbar degenerative diseases. However, comprehensive results of DLIF have not been reported in Korea yet. The object of this study is to summarize radiological and clinical outcomes of our DLIF experience. METHODS: We performed DLIF for 130 patients from May 2011 to June 2013. Among them, 90 patients, who could be followed up for more than 6 months, were analyzed retrospectively. Clinical outcomes were compared using visual analog scale (VAS) score and Oswestry Disability Index (ODI). Bilateral foramen areas, disc height, segmental coronal and sagittal angle, and regional sagittal angle were measured. Additionally, fusion rate was assessed. RESULTS: A total of 90 patients, 116 levels, were underwent DLIF. The VAS and ODI improved statistically significant after surgery. All the approaches for DLIF were done on the left side. The left and right side foramen area changed from 99.5 mm(2) and 102.9 mm(2) to 159.2 mm(2) and 151.2 mm(2) postoperatively (p<0.001). Pre- and postoperative segmental coronal and sagittal angles changed statistically significant from 4.1° and 9.9° to 1.1° and 11.1°. Fusion rates of 6 and 12 months were 60.9% and 87.8%. Complications occurred in 17 patients (18.9%). However, most of the complications were resolved within 2 months. CONCLUSION: DLIF is not only effective for indirect decompression and deformity correction but also shows satisfactory mechanical stability and fusion rate.